Intertrochanteric hip fracture in an arthrodesed hip treated by a LCP condylar plate - Cardile, Carlo; Cazzaniga, Carlo; Manzini, Beatrice; Marasco, Roberto; Ragni, Paolo (Acta Biomedica Atenei Parmensis, 2021)
We report the case of an intertrochanteric hip fracture in a 73 years-old woman with a long-standing arthrodesis. The proper surgical treatment is controversial but we decided to treat the fracture with a single LCP condylar plate turned upside-down. After one year the patient achieved her preinjury levels of activities. This kind of fracture could be satisfactorily treated with locking plate.